Protozoan diseases – a marginalized threat of modern civilization - Marta Sarnowska; Małgorzata Tarnowska; Anna Leśków; Andrzej Wysocki; Marek Pieńkowski; Joanna Rosińczuk (Journal of Education, Health and Sport, 2018)
Globalization and the intensification of tourism in tropical and subtropical areas as well as journeys within the framework of military missions often cause the spread and persistence of infectious and parasitic diseases in areas where they previously have not been reported. Protozoan diseases may also be introduced along with imported, often illegally, exotic animals. Parasitic diseases transmitted from subtropical and tropical regions include protozoan gastrointestinal disorders, such as amoebiasis, balantidiasis and blood protozoan diseases such as malaria, babesiosis, trypanosomiasis, or protozoan diseases of the skin, e.g. leishmaniasis. The aim of the study is to draw attention to the problem of disregard for the risks caused by the development of tourism to tropical countries. One has to bear in mind that being infected with blood protozoan parasites is particularly important for public health because it permanently or temporarily excludes those infected as potential blood donors; this applies to trypanosoma, babesiosis and malaria infections. One should presume that the number of cases of parasitic blood diseases in Poland has increased significantly in comparison with previous years. It should also be emphasized that in connection with diagnostic difficulties in diseases caused by parasitic protozoa, it is possible that these diseases may fail to be diagnosed, thus resulting in an incorrect treatment or a lack thereof. This applies to Trypanosoma infections, babesiosis and malaria.